Perbandingan Sistem Pendidikan Brunei Darussalam dan Indonesia - Sakri, Sakri; Komarudin Sassi; Hoyriah, Ulfa (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2024)
The progress of a country is certainly accompanied by progress in the world of education. The better the quality of education, the better the quality of the human resources it produces. On the other hand, if the quality of education is low, the human resources produced will also be low. The role of education in advancing a country is so important, various ways are needed to advance education. For a nation that wants to progress, education must be seen as inseparable from the role of a nation's progress. Of course, a nation's education has different educational conditions, both in terms of history, education system and policy. Two countries, namely the Unitary Republic of Indonesia and Brunei Darussalam as Islamic countries, always follow developments in educational issues in advancing a nation. In line with that, the education systems in Brunei Darussalam and Indonesia have many differences. If Indonesia wants to develop in terms of education, Indonesia must learn a lot from developed countries, one of which is Brunei Darussalam.